Photonic thermal management of coloured objects. Issue 1 (December 2018) - Li, Wei; Shi, Yu; Chen, Zhen; Fan, Shanhui
Abstract The colours of outdoor structures, such as automobiles, buildings and clothing, are typically chosen for functional or aesthetic reasons. With a chosen colour, however, one must control the radiative thermal load for heating or cooling purposes. Here we provide a comprehensive calculation of the tunable range of radiative thermal load for all colours. The range exceeds 680 Wm−2 for all colours, and can be as high as 866 Wm−2, resulting from effects of metamerism, infrared solar absorption and radiative cooling. We experimentally demonstrate that two photonic structures with the same pink colour can have their temperatures differ by 47.6 °C under sunlight. These structures are over 20 °C either cooler or hotter than a commercial paint with a comparable colour. Furthermore, the hotter pink structure is 10 °C hotter than a commercial black paint. These results elucidate the fundamental potentials of photonic thermal management for coloured objects. Understanding the tunable range of radiative thermal load for a given colour is important for thermal management of outdoor structures. Here, the authors theoretically and experimentally highlighted all mechanisms through which one can control the radiative thermal load of coloured objects.